Clinical and epidemiological features of acute follicular conjunctivitis with special reference to that caused by herpes simplex virus type 1. Issue 9 (1st September 2000) - Uchio, Eiichi; Takeuchi, Satoshi; Itoh, Norihiko; Matsuura, Noriko; Ohno, Shigeaki; Aoki, Koki
Abstract : BACKGROUND/AIMS: It is reported by the national surveillance of ocular infectious diseases in Japan that 4.3% of cases of epidemic keratoconjunctivitis (EKC) diagnosed clinically were caused by herpes simplex virus (HSV). Clinical and virological studies of patients with HSV conjunctivitis were carried out. METHODS: The study population consisted of 478 patients with acute follicular conjunctivitis. Virological analysis was carried out for adenovirus (Ad) and HSV by the cell culture method and fluorescein antibody (FA) method. Polymerase chain reaction for Chlamydia trachomatis was also carried out. RESULTS: From 23 patients, HSV type 1 was isolated but Ad or C trachomatis was not isolated. 87% of cases were unilateral. Most cases showed clinical resolution within 9 days. Early corneal lesions and preauricular lymphadenopathy were less frequent in HSV conjunctivitis than in adenoviral conjunctivitis, especially that due to subgenus D. No case showed a positive result for HSV by the FA method using conjunctival swabs; however, the FA test was positive in all strains isolated by cell culture. CONCLUSIONS: These results indicate that it is difficult clinically to differentiate HSV conjunctivitis from adenoviral conjunctivitis in the acute stage, since the clinical features of adenoviral conjunctivitis are similar to those of HSV conjunctivitis. A biological difference may exist between HSV strains causing keratitis and conjunctivitis.